Lung ultrasound in the evaluation of pulmonary edema in newborns with critical congenital heart disease - Basak Kaya; Dilek Dilli; Yasin Sarikaya; Hasan Akduman; Rumeysa Citli; Utku A. Orun; Mehmet Tasar; Aysegul Zenciroglu (Pediatrics and Neonatology)
Background: Newborns with critical congenital heart disease (CCHD) with increased pulmonary blood flow (PBF) are at high risk for congestive heart failure. In this study, we aimed to evaluate the presence and degree of pulmonary edema in newborns with CCHD using lung ultrasound (LUS) during the perioperative period. Methods: Prospective clinical trial, 44 newborn patients with CCHD were evaluated in this prospective clinical trial. LUS was repeatedly performed to determine the course of pulmonary edema during the perioperative period. LUS was performed simultaneously with chest radiography (CXR), which was the main part of patient management. The primary outcome of this study was to identify whether a correlation existed between LUS and CXR findings. The secondary outcomes were to determine the relationship between LUS and the need for respiratory support, diuretic use, vasoactive inotropic score (VIS), and pro-B-type natriuretic peptide (pro-BNP) levels during the perioperative period. Results: The mean gestational age of the patients was 38.3 ± 1.7 weeks, with a mean birth weight of 3026 ± 432 g. In the preoperative period, both LUS and CXR images were consistent with clinical signs of pulmonary edema. On the first postoperative day, pulmonary edema increased compared to the preoperative period but gradually decreased by the 6th day of surgery (p < 0.05). Positive correlations were observed between the LUS and CXR findings at all study points (p < 0.05). The LUS findings exhibited trends parallel to those of VIS, serum pro-BNP levels, need for respiratory support, and diuretic requirements. As expected, these trends were more pronounced in CCHDs where PBF increased. Conclusion: In CCHD, serial lung ultrasound (LUS) assessments, particularly in cases with increased PBF, can provide valuable guidance for managing patients during the perioperative period.